If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3 = 2y Reorder the terms: -3 + 10x = 2y Solving -3 + 10x = 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 10x = 3 + 2y Combine like terms: -3 + 3 = 0 0 + 10x = 3 + 2y 10x = 3 + 2y Divide each side by '10'. x = 0.3 + 0.2y Simplifying x = 0.3 + 0.2y
| 4(2x-10)=48 | | 13x=150+8x | | 3x-5(-4x-4)=-164 | | y^2-y-12/16-y^2 | | 5/2x+8/x | | 5x+31=73+3x | | 4(2y-5)=12 | | 7(g-4)=4 | | x*8+20=x*4+84 | | 4x^2+200x+4800=0 | | 2x+7(-2x-15)=-33 | | 0.40x-5=23 | | 61-4x=23x+22 | | -55=49x | | x/2+1/2+x/4-3/4=2 | | -8x+4=26x+1 | | 6-7x=61-42x | | (x+4)(x-12)=x(x-9) | | 3(x-7)-4=-19 | | 10x+15-20x=5 | | -68-6x=9x+17 | | w+(w+10)+50=180 | | 44-5x=4x+21 | | 10a-14+6=-12 | | x^2-9x+18/2x^2-9x+9 | | 20-x=5 | | -8x+4=26x-1 | | 7x-14=5x+42 | | ln(x-4)=2 | | 118-2x=43x+18 | | 1/2ln(5x)=4 | | 14k-6-10k=6 |